Visual Aids for Sunscreen Application: A mixed methods study. Issue 1 (15th June 2022) - Julian, Anne K.; Tribby, Calvin P.; Perna, Frank M.
Abstract: Background: Consumers routinely underapply sunscreen, and this may be because they misinterpret application quantity directions on sunscreen labels. U.S. labels use ambiguous terms such as "apply generously" to communicate application quantity. Visual aids may be helpful to consumers to determine proper application quantity. Purpose: To examine sunscreen application practices and sunscreen quantity visual aid preferences. Methods: Sets of five GIFs and five static images were created corresponding to five quantities of sunscreen. Participants extracted their typical‐use sunscreen quantity from a pre‐measured tube and answered questions about their estimation process and use of labeled instructions. Participants then identified their typical‐use sunscreen quantity in response to three stimuli: teaspoons, images, and GIFs and reported their preferred format. Results: No participants reported using the label directions for application quantity to inform their sunscreen use. The GIF‐based visual aid for sunscreen application quantity (44%) was preferred over image‐based (40%) or teaspoon‐based (16%) versions ( p  = .0249). Addition of a GIF demonstration to clarify application quantity was reported as highly helpful. Conclusion: Consumers have difficulty determining the appropriate quantity of sunscreen to use and labeling does not influence their application quantity. A QR code incorporating an image or GIF demonstration of proper sunscreen quantity could be useful to sunscreen consumers.